Indoor microbiological contamination in children day care centres – the ENVIRH study - Cano, Manuela (2015)
In developed countries, after their homes, the children day care center (CDCC) is the place where children spend most of their time, so it is important to understand how environmental factors influence children respiratory health. The aim of ENVIRH (Environment and Health in children day care centres) study is to gather information on indoor environment in CDCC in order to correlate it with both ventilation and children’s health. This paper presents field measurements of indoor microbiological parameters, performed in 19 CDCC during spring and winter and aims to characterize the indoor environment. Bacteria and fungi were collected using a MAS-100 impactor with Trypticase Soy Agar, MacConkey Agar and Malt Extract Agar as culture media for total bacteria, Gram-negative bacteria and fungi, respectively. Concentrations were calculated and fungi were identified. Dust samples were collected on filters using a vacuum cleaner with a DustreamTM collector. Concentration of Der p1 and Der f1 dust mite allergens were assayed separately by ELISA quantitative kit. Most of the CDCC revealed bacterial levels above the reference levels defined by the Portuguese legislation. Nurseries presented lower bacterial concentrations than activity rooms. Indoor fungal concentrations were above outdoor levels in 50% of the studied rooms and the predominant mould genera detected in both seasons were Penicillium and Cladosporium. In spring were obtained higher concentrations of house dust mites in dust with 16% of the rooms surpassing the sensitization threshold.